Developing Students’ Intrinsic Interest in Reading Challenging Articles: An Application of Basic Psychological Need Supports - Kastuhandani, Fidelis Chosa; Ke, Sambo (Sukma: Jurnal Pendidikan, 2022)
Intrinsic motivation in doing academic tasks were important psychological aspects for improvement of students’ learning. However, intrinsic motivation in reading research articles was observably low among Cambodian undergraduate students. Therefore, developing or sustaining their intrinsic motivation was a needed treatment to enhance students’ learning. Self-Determination Theory (SDT) posited that intrinsic motivation could be increased when students are satisfied with Basic Psychological Needs (BPNs) which may be cultivated through learning environments that make them feel competent, autonomous, and relative to the others while doing an academic task. This study intended to examine whether BPN supportive learning environment is salient to increase intrinsic motivation in reading a research article. 27 participants who were undergraduate students and enrolled in a course of community psychology were purposively selected to fill in a self-administrative questionnaires of Intrinsic Motivation Inventory before and after attending the reading activity. As a result, level of intrinsic motivation in reading was increased in 10 units (64.74 to 74.44) after the activity finished. It was concluded that BPN supportive learning environment was important to increase or at least sustain intrinsic motivation among these particular students. The implication of this study result in the classroom practices was discussed under the SDT perspectives.